Peningkatan Pemahaman Konsep Bangun Datar Melalui LKPD Bernuansa Etnomatematika di Kelas IV SD 2 Jati Wetan - Fitriani, Avisha; Zuliana, Eka; Vebriani, Niasari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The aim of this research is to see how an ethnomathematics approach can improve students' understanding of mathematical concepts at SD 2 Jati Wetan. This research is classroom action research carried out in two cycles with a sequence of planning, action, observation and reflection stages. The research subjects were class IV students. Data is collected by observation and tests. The data analysis used is qualitative and quantitative data analysis. The results of the research show that the ethnomathematics approach is able to increase students' understanding of mathematical concepts at SD 2 Jati Wetan. The increase in understanding of concepts can be seen from: The results of the research show that understanding of mathematical concepts increased from 53% (poor) in cycle I to 80% (good) in cycle II. Teachers' teaching skills also increased from 75% (good) to 88% (very good). Student learning activity increased from 73% (good) to 86% (very good). From this research, it can be concluded that the ethnomathematics approach is able to improve the ability to understand mathematical concepts in flat shape material in class IV students.